The state of teaching and learning during the outbreak of COVID-19 in East African Universities - Edward, Ombui; Tandika, Pambas; Fabian, Flora; Mongi, Hector; Moshi, Fabiola; Muchungi, Kendi; Mukami, Victoria; Kiguru, Mary (My University, 2024)
The primary concern about interruptions in teaching and learning in higher education institutions is no longer a question of internal conflicts like student strikes or staff demonstrations but whether universities and colleges are cultivating a resilient institutional culture to mitigate, adapt to, and survive external and global interruptions such as COVID-19. Respective government directives compelled East African learning institutions to abruptly terminate in-person learning in March 2020 in the wake of COVID-19 in the region. Instructors and university management officers of the sampled universities in Tanzania and Kenya shared their experience through individual and face-to-face interviews on the knowledge and skills of the instructors on alternative modalities of managing teaching and learning during this period? This study uses descriptive analysis to provide an in-depth understanding of the state of teaching and learning during COVID-19 pandemic in East African Universities. The analysis reveals that despite initiative invested by university management in training instructors for different modalities of teaching and learning, instructors were reluctant to adopt an online model of instruction. Consequently, workload increased after re-opening of the universities with development of policy guidelines and conducting research for appropriate ways of managing universities during pandemic being suggested.
The state of teaching and learning during the outbreak of COVID-19 in East African Universities
Keywords: Pandemic; COVID-19; Teaching and Learning; Instructors; University Management; East African Universities